English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

You have a lot of answers to your equations questions, but clearly have missed the method. Here is the elimination method.

The idea is to multiply one equation by a number so that the coefficient of one variable (the number in front of the variable) is the same in both equations. In this case, we can multiply the second equation by 2 (which doesn't change the equation)

Original second equation:
4x + 1 = 3y
Multiply both sides by 2
8x + 2 = 6y

Now, both equations have the same coeffient for x: 8. So, we just subtract one equation from the other:
8x - 1 = 4y
8x + 2 = 6y
---------------
-3 = -2y

Divide by -2 and we get
-3/-2 =y or
3/2 = y

Now take the value of y and back substitute it into any of your equations to find x:
8x - 1 = 4(3/2)
8x - 1 = 6
8x = 7
x = 7/8

You should check your answer by putting the x and y values in the other equation and make sure it is true.

Sometimes you need to multiply BOTH equations by a number to get the same coeffient, but the process is the same.

2007-01-01 14:51:08 · answer #1 · answered by grand_nanny 5 · 0 0

I will give you one fool-proof method

8x-1=4y
4x+1=3y

rewrite one equation :
8x-1=4y
thus y = 1/4 * (8x - 1 )

substitute ( REPLACE) the y in the second equation with your rewritten eqaution :
this you have
4x+1=3y

replace the y with y = 1/4 * (8x - 1 )

4x+1=3*1/4 * (8x - 1 )

no write the x explicit and you have the x value.
the y value yo will get by
well you should know by now

2007-01-02 05:46:13 · answer #2 · answered by gjmb1960 7 · 0 0

fedest.com, questions and answers